Outcomes of Elastic Stable Intramedullary Nailing for Pediatric Femoral Shaft Fractures: A Retrospective Study of 25 Cases - Tuyen, Nguyen Trung; Trinh, Le Khanh; Hai, Nguyen Ba; Hieu, Nguyen Dinh (VNU Journal of Science: Medical and Pharmaceutical Sciences; Acticle in PressDO - 10.25073/2588-1132/vnumps.5044, 2026)
Background: Elastic stable intramedullary nailing (ESIN) is widely used for pediatric femoral shaft fractures because it allows minimally invasive fixation and early mobilization. Objective: To evaluate the outcomes of ESIN for pediatric femoral shaft fractures. Methods: A retrospective case series was performed on 25 children aged 4–15 years with closed femoral shaft fractures treated using ESIN between January 2023 and January 2024. Clinical and radiographic outcomes were assessed with a minimum follow-up of 6 months. Results: The mean age was 11.7 ± 2.3 years, and 68% of patients were male. Midshaft fractures accounted for 60% of cases. Radiographic union was achieved in all patients. One patient developed superficial wound infection. According to Flynn’s criteria, 80% of patients had excellent outcomes and 20% had satisfactory outcomes. Conclusions: ESIN is a safe and effective treatment option for pediatric femoral shaft fractures, providing high union rates, favorable functional outcomes, and low complication rates.